The Effect of Remuneration, Work Discipline and Motivation on Employee Performance - Paulus, P. (Manunggal Halim Jaya, 2023)
The success and failure of activities within an organization are measured based on the performance of its employees. This performance can be influenced by various factors, such as remuneration, work discipline, and motivation. The purpose of this study is to analyze the effect of these three factors on the performance of employees at Office of Syahbandar and Port Authority (KSOP) Class IV Sintete West Kalimantan. This research uses a census method with a total of 70 respondents from the population related to the performance of employees at Office of Syahbandar and Port Authority (KSOP) Class IV Sintete West Kalimantan. Multiple regression analysis is used to analyze the data. The results of the study show that remuneration, work discipline, and motivation have a positive and significant influence on employee performance simultaneously. Specifically, work motivation is found to have the most dominant influence on employee performance. These findings suggest the importance of managing remuneration and motivation in improving employee performance. Work discipline also plays a crucial role in enhancing employee performance. However, it should be noted that this study has limitations in terms of its measurement and analysis techniques and its generalizability to other organizations. Further research could be conducted to expand understanding and explore other factors that affect employee performance.